PUBLIC DEBT, BANKS AND MONETARY POLICY TRANSMISSION: AN EMPIRICAL ASSESSMENT OF THE INFLATION TARGETING IN BRAZIL - Fonseca, Marcos Wagner da (2013)
This paper aims to discuss whether there is obstruction in the transmission mechanism and, consequently, ineffectiveness of monetary policy in Brazil post-inflation targeting system. For this, the work begins with a descriptive analysis that showed that after the adoption of inflation targeting system, there was a change in the composition of public debt and consolidation of the banking sector, which indicates that monetary policy followed a path of gain effectiveness of monetary transmission and have effective participation in this gain. Broke up, then, for empirical analysis, with the application and estimation of VAR models for the whole period (1996 to 2007) and for the inflation targeting period (2000 to 2007). The results indicate that there is a difference when taking only the inflation targeting period. It was noticed a non-negligible change in the variables behavior between the estimated models for the two periods. The results for the inflation targeting period suggest that there were gains in effectiveness of monetary policy to determine changes in output and inflation. The banks behavior indicates that there is no clear obstructions caused by them in monetary transmission.